Faktor Pendukung Pemanfaatan Jaminan Kesehatan Nasional Untuk Penanganan Penyakit Katastropik Di Indonesia - Widayati, Hesti Prawita; Intiasari, Arih Diyaning; Rejeki, Dwi Sarwani Sri (Jurnal Biomedika dan Kesehatan, 2025)
The National Health Insurance (Jaminan Kesehatan Nasional/JKN) is a nationwide program that applies social insurance principles to provide equitable access to healthcare services, including coverage for catastrophic illnesses that entail high medical expenditures. Despite its extensive coverage, the use of JKN for the management of devastating illness is influenced by various socioeconomic and health-related factors. This study aimed to identify determinants of JKN utilization for the management of catastrophic diseases in Indonesia. This systematic review was conducted using the PRISMA guidelines. Literature searches were performed across four electronic databases: PubMed, PubMed Central, Semantic Scholar, and Google Scholar. Articles were included if they discussed factors influencing the utilization of JKN or other national health insurance schemes for catastrophic illnesses. Exclusion criteria excluded studies that did not address catastrophic disease management or were not relevant to insurance utilization. The review focused on publications issued between 2015 and 2025. The initial search identified 678 articles, which were screened using title, abstract, and full-text reviews, as well as duplicate checks. A total of six articles met all eligibility criteria for final analysis. The included studies consistently showed that several factors supported JKN utilization in the management of catastrophic illness. These determinants comprised household income, family size, marital status, gender, age, medical costs, and the presence of chronic illness. Evidence indicated that low-income households, larger families, older individuals, and those with chronic diseases were more likely to rely on national health insurance due to high financial vulnerability. This review concluded that key socioeconomic and health-related factors influence the use of JKN for the management of catastrophic illness in Indonesia. Strengthening JKN policies and enhancing financial protection mechanisms are essential to reducing the economic burden of devastating diseases and ensuring the program's long-term sustainability.